Preparation method of polyester based on tetragonal system germanium dioxide catalyst
The preparation of tetragonal germanium dioxide catalysts via a hydrothermal method solves the problem of insufficient catalytic activity in hexagonal germanium dioxide, enabling efficient polyester synthesis and the production of high-performance polyester products that meet the requirements of high-end optical materials.
Patent Information
- Application Number
- CN202511675015.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-03-17
AI Technical Summary
The catalytic activity of existing germanium-based polyester catalysts (mainly hexagonal germanium dioxide) needs to be improved, resulting in a slow polyester synthesis reaction rate, high production cost, and insufficient overall performance of polyester products such as transparency, color and thermal stability, making it difficult to meet the needs of high-end optical applications.
A tetragonal germanium dioxide catalyst was synthesized by hydrothermal method. By controlling the reaction time and solution pH, a catalyst with a regular polyhedral structure and more surface oxygen vacancy defects was prepared. The catalyst was then used in the polycondensation reaction to prepare polyester.
It significantly improves catalytic activity, enhances the intrinsic viscosity, transmittance, color, and thermal stability of polyester, and reduces production costs, making it suitable for the production of high-end optical materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing polyester based on a tetragonal germanium dioxide catalyst, belonging to the field of polyester catalyst technology. Background Technology
[0002] Germanium, located in Group 4, is low in toxicity, and its oxides exhibit good stability. Polyesters prepared using germanium-based catalysts exhibit high transparency, excellent color purity, and are far superior to those prepared using other catalyst systems. This study investigated the effects of antimony trioxide, tetrabutyl titanate, and germanium dioxide as polycondensation catalysts on the properties of PET chips. The results showed that the GeO2 catalyst had slightly lower catalytic activity than antimony-based and titanium-based catalysts, but its products exhibited lower yellowness, higher transparency, and better thermal stability. Currently, high-end optical polyester films and other products are prepared using germanium-based catalysts. However, germanium is relatively rare and expensive, limiting its application. Therefore, improving the catalytic activity of germanium-based catalysts can effectively reduce their usage, shorten production time, and significantly reduce costs. Currently, research on germanium-based catalysts is limited, with studies on Ge primarily focusing on composite synergy and rarely considering crystal form. However, germanium is the most effective catalyst for preparing high-end optical polyester products; therefore, improving the catalytic activity of germanium-based polyester catalysts is of great significance for high-end polyester production.
[0003] Metal oxides combine through different connection methods, resulting in a variety of complex crystal structures. Structure determines properties, leading to significant differences in physicochemical properties among metal oxides with different crystal structures. The crystal structure of a catalyst has a decisive impact on its activity, selectivity, and stability. Crystal structure directly affects the exposure of active sites and the kinetic characteristics of reaction pathways by altering atomic arrangement, surface energy distribution, and electron migration paths. Different crystal structures have unique atomic arrangements, leading to differences in the exposure ratio of specific crystal faces, and different crystal faces exhibit different catalytic activities for specific reactions. For example, the {101}, {010}, or {001} crystal faces of titanium dioxide (TiO2) show different photocatalytic activities for the photodegradation of methyl orange; the photocatalytic activity of {001}-TiO2 is 1.79 times and 3.22 times higher than that of {010} and {101}-TiO2, respectively. Different crystal structures also have different electronic structures; crystal structure transformation leads to changes in the positions of energy bands and conduction bands. By studying three different crystalline forms of TiO2, it was found that the high photocatalytic hydrogen activity of brookite is due to the structural advantage of its higher conduction band and lower valence band, resulting in a high yield of hydroxyl radicals. Different crystalline forms lead to different catalyst structures, resulting in varying effects on the adsorption and diffusion of reactants. The influence of different crystalline forms of MnO2 on the decomposition ability of O3 was also investigated. The results showed that the activity order for O3 decomposition by different crystalline forms was α-MnO2 > γ-MnO2 > β-MnO2. This is because α-MnO2 manganese oxide has a larger specific surface area and a lower oxidation state, thus it is more easily adsorbed by O3 and easily oxidized by O3. Furthermore, the morphology and oxygen defect vacancies of different crystalline catalysts generally also differ. In conclusion, the influence of crystal form on catalysis is multifaceted.
[0004] Studies have also explored the impact of crystal structure on catalysis in polyester production. Initially, antimony trioxide was often used and contained various crystal forms, resulting in low purity of the active component and consequently poor catalytic activity. Therefore, investigating the effect of the crystal structure of metal oxide polyester catalysts on the catalytic efficiency of the polycondensation process is crucial in polyester catalyst research. Through this research, the catalyst with the highest catalytic activity can be selected, thereby improving polyester production efficiency. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing polyester based on tetragonal germanium dioxide catalyst, in order to solve the problems of the need to improve the catalytic activity of existing germanium-based polyester catalysts (mainly hexagonal germanium dioxide), and the resulting relatively slow polyester synthesis reaction rate and high production cost; at the same time, it further improves the comprehensive performance of the synthesized polyester product, such as intrinsic viscosity, transmittance, color and thermal stability, to meet the needs of high-end optical applications.
[0006] The tetragonal germanium dioxide catalyst used in this invention is synthesized via a hydrothermal method. It has a regular polyhedral structure and a particle size of 400-500 nm. The specific steps are as follows: 1) Disperse hexagonal germanium dioxide raw material in an acidic aqueous solution to form a reaction mixture; 2) The reaction mixture is placed in a hydrothermal reactor to carry out a hydrothermal reaction to obtain the final product; The conditions for the hydrothermal reaction are as follows: The reaction temperature is 120℃-240℃, the reaction time is 24-48h, and the pH value is 1-3.
[0007] Preferably, before dispersing the hexagonal germanium dioxide raw material in the acidic aqueous solution, the method further includes a step of calcining the hexagonal germanium dioxide raw material for pretreatment. The calcination pretreatment conditions are calcination at 500-600℃ for 4-8 hours, preferably calcination at 550℃ for 6 hours; The hydrothermal reaction temperature is 120℃-80℃.
[0008] Preferably, the conditions for the hydrothermal reaction are as follows: The reaction temperature was 240℃, the reaction time was 36h, and the pH value was 3. By precisely controlling the reaction time and solution pH, the morphology and size of the product can be controlled. A reaction time that is too short (e.g., 12 hours) will not form a tetragonal crystal phase; extending the time to 36 hours will yield a regular polyhedral structure; and further extending it to 48 hours will result in uneven particle size. pH has a significant impact on morphology; at pH=1, long prismatic rod-like structures are easily formed, while at pH=2 and pH=3, regular dodecahedral particles are easily formed, and the particles obtained at pH=3 are smaller and more uniform in size. The acidic aqueous solution is an aqueous solution of sulfuric acid.
[0009] The tetragonal germanium dioxide catalyst provided by this invention has more surface oxygen vacancy defects (confirmed by XPS analysis). These oxygen vacancies serve as active sites, significantly improving its catalytic efficiency for the PET polycondensation reaction. Based on the aforementioned tetragonal germanium dioxide catalyst, the present invention provides a method for preparing polyester, comprising the following steps: S1, a dicarboxylic acid and a diol are esterified to obtain an esterified product; S2. Under the presence of a catalyst, the esterification product undergoes a polycondensation reaction to obtain a polyester. The dicarboxylic acid is terephthalic acid; the diol is ethylene glycol.
[0010] Preferably, the conditions for the polycondensation reaction are as follows: The amount of catalyst used is 0.10‰-0.30‰ of the mass of oxalic acid, preferably 0.20‰, the temperature is 270℃-290℃, preferably 280℃, the time is 3.0-4.5 hours, preferably 3.5 hours, and the process is carried out under vacuum conditions.
[0011] The polyester provided by this invention has an intrinsic viscosity of not less than 0.425 dL / g; The polyester has at least one of the following optical properties: Light transmittance not less than 82%; Yellowness b value not higher than 4.5; Whiteness L value not less than 92; The polyester has at least one of the following thermal properties: The glass transition temperature is not lower than 68℃; The cold crystallization temperature should not exceed 127℃; Melting point not lower than 247℃; The crystallinity measured by differential scanning calorimetry is no higher than 12%.
[0012] The present invention has the following beneficial effects: High catalyst activity: Tetragonal germanium dioxide was successfully prepared by crystal form control. Its surface has more oxygen vacancies, which provide abundant active sites. Its catalytic activity is significantly higher than that of traditional hexagonal germanium dioxide. Under the same conditions, it can increase the intrinsic viscosity of PET by about 6.7%.
[0013] Excellent product performance: The PET polyester synthesized using the catalyst of this invention has the advantages of high molecular weight, good transparency, excellent color, and strong thermal stability, and is particularly suitable for high-end optical films and other fields.
[0014] Significant economic benefits: The improved catalyst activity means that when producing PET products with the same performance, the amount of expensive germanium catalysts can be reduced, or the reaction time can be shortened, thereby effectively reducing production costs and promoting the industrialization of high-end polyester. Attached Figure Description
[0015] Figure 1 These are images depicting the morphology and particle size distribution of germanium dioxide. In the image, (a) shows the morphology of hexagonal germanium dioxide, (b) shows the particle size distribution of hexagonal germanium dioxide, (c) shows the morphology of tetragonal germanium dioxide, and (d) shows the particle size distribution of tetragonal germanium dioxide.
[0016] Figure 2 These are XPS spectra of germanium dioxide structures with different crystal forms, where (a) is C1s, (b) is O1s, (c) is Ge2p, and (d) is Ge3d.
[0017] Figure 3This is a simplified diagram of the apparatus for the esterification step.
[0018] 1. Electric heating mantle; 2. Three-necked flask; 3. Thermometer; 4. Stirring rod; 5. Cantilever stirrer; 6. Thermometer; 7. Distillation head; 8. Distillation column; 9. Straight condenser; 10. Horn tube; 11. Graduated cylinder.
[0019] Figure 4 This is a simplified diagram of the apparatus for the polycondensation step.
[0020] 12. Nitrogen cylinder; 13. High-temperature and high-pressure reactor; 14. Safety bottle; 15. Vacuum gauge; 16. Vacuum pump.
[0021] Figure 5 These are FT-IR images of PET synthesized using GeO2 catalysts with different crystal forms.
[0022] Figure 6 This is a transmittance diagram of PET synthesized using GeO2 catalysts with different crystal forms.
[0023] Figure 7 This is a chromaticity diagram of PET synthesized using GeO2 catalysts with different crystal forms.
[0024] Figure 8 These are TGA spectra of PET synthesized using GeO2 catalysts with different crystal forms.
[0025] Figure 9 These are DTG spectra of PET synthesized using GeO2 catalysts with different crystal forms.
[0026] Figure 10 These are DSC spectra of PET synthesized by GeO2 catalysts with different crystal forms. Among them, (a) is the heating curve of PET1, (b) is the heating curve of PET2, (c) is the cooling curve of PET1, and (d) is the cooling curve of PET2.
[0027] Figure 11 These are XRD patterns of different PET samples. Detailed Implementation
[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0029] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0030] This invention aims to address the shortcomings of existing germanium-based polyester catalysts (primarily hexagonal germanium dioxide), which require improved catalytic activity and result in relatively slow polyester synthesis rates and high production costs. Furthermore, this invention aims to further enhance the overall performance of the synthesized polyester products, such as intrinsic viscosity, transmittance, color, and thermal stability, to meet the demands of high-end optical applications.
[0031] This invention employs a novel, highly efficient germanium-based polyester catalyst: tetragonal germanium dioxide (GeO2), which is prepared by a hydrothermal method. The preferred reaction conditions are: reaction temperature 240℃, reaction time 36 hours, pH value of the reaction system 3, and the raw materials are calcined.
[0032] This invention provides a method for preparing high-performance polyethylene terephthalate (PET), comprising esterification and polycondensation steps. The key aspect is the use of tetragonal germanium dioxide as a catalyst in the polycondensation reaction. Preferred process parameters are as follows: Catalyst dosage: 0.20‰ (relative to the mass of PTA terephthalic acid); final polycondensation temperature: 280℃; polycondensation time: 3.5 hours.
[0033] This invention provides a high-performance PET polyester prepared by the above method, which has excellent overall properties.
[0034] The present invention has the following significant advantages: The catalytic efficiency was significantly improved: under the same reaction conditions, the intrinsic viscosity of the obtained PET polyester increased from 0.402 dL / g to 0.429 dL / g, indicating that the molecular weight was higher and the polymerization reaction was more complete.
[0035] The product boasts superior optical properties: the light transmittance of PET polyester is increased to 82.3%, the chromaticity b value (yellowness) is reduced to 4.45, and the L value (whiteness) is as high as 92.2, resulting in a purer and more transparent color that meets the stringent requirements of high-end optical materials for light transmittance.
[0036] Enhanced thermal stability: Thermogravimetric analysis (TGA) shows that the 5% weight loss temperature of the product is higher, and the temperature corresponding to the maximum weight loss rate is also higher, indicating that it has better thermal stability and fewer side reactions.
[0037] This invention successfully developed a high-performance tetragonal germanium dioxide polyester catalyst using crystal engineering strategies. This catalyst not only exhibits high activity, effectively shortening reaction time and reducing germanium consumption, thereby directly lowering production costs, but also enables the production of high-end PET polyester products with comprehensive performance far exceeding existing technologies. This invention provides crucial technical support for the polyester industry, particularly for the high-quality production of high-end optical polyester films, and has significant theoretical implications and broad prospects for industrial application.
[0038] The following raw materials were used in the following embodiments: Phenol, AR, purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.; 1,1,2,2-Tetrachloroethane, AR, 98%, purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.; Chloroform, 99.5%, Beijing Chemical Plant; Potassium hydroxide (KOH), 95%, purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.; Bromophenol blue, AR, purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.; Nitrogen (N2), 99.5%, Beijing Huanyu Jinghui Jingcheng Gas Technology Co., Ltd.; Hexagonal germanium dioxide purchased from Yunnan Chihong International Germanium Co., Ltd.
[0039] The detection methods in the following embodiments are as follows: intrinsic viscosity ([ η Test: Weigh 0.125 g of PET product and add it to a flask containing 25 mL of a mixed solution of phenol and 1,1,2,2-tetrachloroethane (mass ratio 50:50). Stopper the flask and allow the PET sample to completely dissolve at 100 °C. Remove the flask and cool it to room temperature. Measure the outflow time using an Ubbelohde viscometer at 25 °C. Calculate the intrinsic viscosity using Equations 1 and 2.
[0040] (1) (2) In the formula: η sp t1 is the specific viscosity; t1 is the flow time of the PET polyester solution in the Ubbelohde viscometer, s; t0 is the flow time of the phenol-tetrachloroethane mixed solution in the Ubbelohde viscometer, s; [η] is the intrinsic viscosity of the polyester, dL / g; c is the concentration of the PET polyester solution, g / 100mL. Color value (L, a, b) test: The color value of the PET polyester sample was determined using a spectrophotometer. Specific procedure: The sample was placed in an oven and heated at 135 ℃ for 30 min. After cooling, it was pulverized and sieved. 20-60 mesh particles were placed in a sample cup and placed over the measuring hole. Under a D65 light source and a 10° viewing angle, the L, a, and b values were measured. After one measurement, the cup was rotated 120° and the measurement was repeated. A total of three measurements were taken, and the average value was recorded.
[0041] Terminal carboxyl group content (X) COOH Test: Weigh 1 g of PET polyester sample and add it to a flask containing 25 mL of a phenol-chloroform mixed solution (phenol to chloroform volume ratio 2:3). Heat under reflux until the sample is completely dissolved. After cooling to room temperature, add 3-4 drops of bromophenol blue ethanol solution (bromophenol blue mass concentration 0.1%) as an indicator. Titrate with potassium hydroxide-ethanol standard titration solution (potassium hydroxide concentration 0.05 mol / L). The titration endpoint is defined as the color changing from yellow to blue. Record the volume of potassium hydroxide-ethanol standard titration solution consumed. Calculate the terminal carboxyl group content using Formula 3.
[0042] (3) In the formula: X COOH V represents the end carboxyl group content of the PET polyester sample, in mol / t; V represents the volume of potassium hydroxide-ethanol standard titration solution consumed by the PET polyester sample solution, in mL; V0 represents the volume of potassium hydroxide-ethanol standard titration solution consumed by the phenol-chloroform mixed solution, in mL; c represents the concentration of the potassium hydroxide-ethanol standard titration solution, in mol / L; and m represents the mass of the PET polyester sample, in g.
[0043] Transmittance (T) Test: The transmittance of PET polyester was measured using a spectrophotometer. Specific procedure: A prepared PET polyester slice was taken, and its thickness was measured using calipers. The spectrophotometer was set to transmittance measurement mode, with a wavelength of 400 nm. Using air as a standard, the spectrophotometer was calibrated to 100% transmittance. The PET polyester slice with its thickness measured was then placed vertically in the light cell, and its transmittance was measured.
[0044] Fourier Transform Infrared Spectroscopy (FT-IR): FT-IR is primarily used for functional group identification and structure determination. Principle: After molecules absorb infrared light, energy level transitions occur. Different functional groups have unique vibrational frequencies, absorbing infrared light at specific wavelengths and forming characteristic absorption peaks. Specific Operation: Dry PET polyester is pulverized. A small amount of PET polyester powder is mixed with potassium bromide to form a sample, which is then placed in a FT-IR spectrometer for testing. The measurement range is 400-4000 cm⁻¹. -1 The resolution is 0.2 cm. -1 .
[0045] Thermogravimetric analysis (TGA) test: TGA test was performed on PET polyester. Specific procedure: 5-8 mg of PET sample was placed in an aluminum crucible, nitrogen was introduced at a rate of 50 mL / min, and the temperature was increased to 600 °C at a rate of 10 °C / min to obtain the TGA curve of PET polyester.
[0046] Differential Scanning Calorimetry (DSC) Test: DSC test was performed on PET polyester. Specific procedure: Take 5~8 mg of PET sample in an aluminum crucible, purge with nitrogen at a rate of 50 mL / min, raise the temperature to 280 ℃ at a rate of 10 ℃ / min, hold for 3 min, and then lower the temperature to 30 ℃ at a rate of 10 ℃ / min.
[0047] The PET polymerization process is complex and generates various side reactions that affect PET crystallization. Furthermore, the inhomogeneity of PET sample crystallinity further influences the PET melting point. The formula for calculating PET crystallinity (x) is shown in Equation 4: (4) In the formula, H m The enthalpy of fusion of the crystalline polymer during melting, in J / g; H c The enthalpy of cold crystallization of a polymer at a certain temperature, expressed in J / g; H 0 represents the theoretical enthalpy of melting for a 100% crystalline polymer. H 0 = 140 J / g.
[0048] Example 1: Tetragonal germanium dioxide was prepared from hexagonal germanium dioxide via a hydrothermal method. The hexagonal germanium dioxide raw material was pretreated by calcining at 550 °C for 6 hours.
[0049] Prepare a sulfuric acid aqueous solution with pH=3. Weigh 0.4 g of hexagonal germanium dioxide and disperse it in 60 mL of sulfuric acid aqueous solution, then place the solution in a hydrothermal reactor. Place the hydrothermal reactor in an electrically heated constant-temperature drying oven at 240 ℃ and react for 36 h. After the reaction, remove the solution, take out the white precipitate, and put the precipitate back into deionized water for ultrasonic water bath dispersion and washing. Centrifuge three times at 5000 r / min to remove sulfuric acid residue. Then, dry the centrifuged powder in a 60 ℃ oven for 24 h to obtain the tetragonal germanium dioxide product.
[0050] Morphological and structural analysis of tetragonal germanium dioxide: To better understand the structural and morphological differences between the raw material hexagonal germanium dioxide and the prepared tetragonal germanium dioxide, and thus facilitate the assessment of catalytic efficiency, a systematic comparative analysis of the two crystalline germanium dioxide forms was conducted using SEM and XPS to examine their morphology and structure.
[0051] The morphology of the hexagonal germanium dioxide reactant and the tetragonal germanium dioxide prepared in this example was analyzed using scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. Figure 1 Figure a shows the SEM image of hexagonal germanium dioxide. It can be seen that the sample has poor dispersibility and exhibits an agglomerated state, consisting of plate-like and blocky stacks. The particle size distribution ranges from 200 nm to 700 nm, as shown in the figure. Figure 1 As shown in Figure b, the distribution basically conforms to a normal distribution, with the particle size distribution mainly concentrated in the range of 300-400 nm. Figure 1Figure c shows the SEM image of tetragonal germanium dioxide synthesized by the hydrothermal method. It can be seen that the sample has poor dispersibility, exhibiting polyhedral aggregates, previously inferred to be mainly dodecahedral. The particle size distribution is relatively dispersed, with a maximum particle size of approximately 700 nm and a minimum particle size of 200 nm. The main particle size distribution range is concentrated in the 400-500 nm range, but a considerable proportion of particles are distributed in the 600-650 nm range. Figure 1 As shown in Figure d.
[0052] Surface state analysis can be performed on hexagonal germanium dioxide, the reactant, and tetragonal germanium dioxide prepared under optimal reaction conditions using X-ray photoelectron spectroscopy (XPS). Figure 2 These are series of XPS spectra of two germanium dioxide samples. Figure 2 As shown, the detection yielded three elements: C, O, and Ge.
[0053] Figure 2 Figure a shows the XPS spectrum of C, with an electron binding energy of 284.8 eV. This C element is mainly used as an internal standard to calibrate the charge energies in O1s, Ge2p, and Ge3d. Figure 2 Figure b shows the analysis of oxygen. The 1s electron binding energies of O in tetragonal and hexagonal germanium dioxide are 531.4 eV and 532.1 eV, respectively. Further analysis reveals that the 1s binding energy of O is provided by the lattice oxygen energy and the adsorbed oxygen energy. Figure 2 In Figure c, because Ge in germanium dioxide is in the +4 valence state, the binding energy of the Ge 2p peak is relatively high. Specifically, the peak positions of the tetragonal germanium dioxide with a binding energy of 1219.7 eV and the hexagonal germanium dioxide with a binding energy of 1220.4 eV are Ge 2p peaks. 4+ Ge2p 3 / 2 Characteristic peak positions; the peak position of tetragonal germanium dioxide with a binding energy of 1250.7 eV and the peak position of hexagonal germanium dioxide with a binding energy of 1251.4 eV are Ge 4+ Ge2p 1 / 2 Characteristic peak position; Ge2p 3 / 2 Characteristic peaks and Ge2p 1 / 2 The peak in the middle of the characteristic peak is a loss peak caused by energy loss due to inelastic collisions between photoelectrons and atoms when they pass through the sample surface. Figure 2 In the d-plot, the peaks at 32.2 eV for tetragonal germanium dioxide and 33.1 eV for hexagonal germanium dioxide originate from Ge3d.
[0054] from Figure 2 It can also be seen that, compared with hexagonal germanium dioxide, the peaks corresponding to O1s, Ge2p, and Ge3d in tetragonal germanium dioxide are shifted by 0.7 eV for O1s and Ge2p for Ge2p.1 / 2 Offset by 0.7 eV, Ge2p 3 / 2 The shift was 0.7 eV, and Ge3d shifted by 0.9 eV. It is speculated that this is due to the different local chemical environment, coordination, and bond length and bond angle of Ge atoms caused by the different crystal structures of tetragonal and hexagonal germanium dioxide. This also shows that tetragonal germanium dioxide was successfully prepared under this hydrothermal condition, which is consistent with the previous XRD results.
[0055] XPS fine spectroscopy has the function of revealing the microscopic features of elemental chemical states, electronic structures, and surface defects at high resolution, thereby locating active sites and revealing structure-activity relationships. Therefore, its value in catalytic materials research is particularly prominent. The elemental XPS fine spectra of two different crystalline forms of germanium dioxide were analyzed proportionally, and the results are shown in Table 2. Table 2 shows that the two GeO2 samples have defects of varying degrees on their surfaces, all caused by the absence of O atoms. Generally, for catalysis, the more oxygen vacancies, the more exposed metal elements, the more active sites can be provided, and the stronger the catalytic activity. Furthermore, the absence of oxygen atoms leads to changes in the electronic structure around the vacancies, thereby improving the adsorption capacity for reactant molecules. Based on the XPS parameter analysis results, the tetragonal GeO2 prepared by hydrothermal synthesis has more oxygen vacancies. From this perspective, it is speculated that the tetragonal germanium dioxide prepared by hydrothermal synthesis will have better catalytic performance than the original hexagonal germanium dioxide.
[0056] Table 2 XPS parameters of two germanium dioxide samples with different crystal forms
[0057] Example 2: Preparation of PET Polyester (1) Esterification reaction: Weigh 46.5 g (0.75 mol) ethylene glycol (EG) and add it to a 250 mL three-necked flask, then add 83 g (0.5 mol) terephthalic acid (PTA). Set up the esterification reaction apparatus, such as... Figure 3 As shown. Nitrogen gas (N2) is introduced into the apparatus to purge the air from the system. The rotation speed is set to 150 r / min, and heating is carried out under normal pressure. The amount of water flowing out of the graduated cylinder is observed. The first drop of water is taken as the starting point of the esterification reaction. The esterification reaction is considered to be complete when a clear spot appears on the reactants. The esterified product BHET is then discharged. During the reaction, the temperature at the top of the fractionation column is controlled not to exceed 120 °C.
[0058] (2) Polycondensation reaction: The product BHET after esterification was weighed and placed in a quartz liner. 0.0131 g (0.25‰) of GeO2 catalyst (prepared in Example 1) was weighed and dispersed in the BHET. The quartz liner was placed in the reactor, sealed, and a polycondensation apparatus was constructed, such as... Figure 4 Open the inlet and outlet valves to introduce N2 into the apparatus and purge the air from the system. Close the inlet and outlet valves, and begin heating the system. Once the temperature reaches 230 °C, turn on the stirrer at 300 r / min and open the vacuum pump and outlet valve. Perform pre-polymerization for 0.5 h, continuously increasing the vacuum level and gradually raising the temperature to 280 °C. Perform the polycondensation reaction at this temperature for 3.5 h, then stop stirring, close the outlet valve, and stop evacuating. Open the nitrogen cylinder and the inlet valve to slowly introduce nitrogen. Discharge the material to prepare PET chips.
[0059] FT-IR analysis of PET polyester: The structures of two samples were analyzed using infrared spectroscopy. One sample was prepared using tetragonal germanium dioxide as a catalyst at a final polycondensation temperature of 280 °C and a catalyst concentration of 0.20‰. The other sample was prepared using hexagonal germanium dioxide as a catalyst at the same conditions. Their FT-IR spectra are shown below. Figure 5 As shown.
[0060] exist Figure 5 Middle, 2920 cm -1 2850 cm -1 1408 cm -1 The absorption peaks at 1715 cm⁻¹ are caused by the asymmetric stretching vibration, symmetric stretching vibration, and bending vibration of the methylene group (-CH₂-), respectively. -1 The absorption peak at 1650-1430 cm⁻¹ is a characteristic peak of the stretching vibration of the carbonyl group (C=O); -1 The absorption peaks that appear intermittently are attributed to the skeletal vibrations of substituted benzene compounds; 1236 cm⁻¹ -1 1090 cm -1 1016 cm -1 The absorption peaks at 725 cm⁻¹ are all caused by the stretching vibrations of the -COC- structure. -1 The peak at that point is caused by the bending vibration of the CH bond.
[0061] Depend on Figure 5 As can be seen, both samples exhibit typical infrared spectral characteristics of aromatic polyesters, and the groups present are also present in PET polyesters. Comparison of the spectra with the standard infrared spectra of PET polyester shows consistent results. Therefore, based on the FTIR spectra, it can be determined that both synthesized samples are PET polyesters.
[0062] Example 3: Evaluation of the catalytic activity of germanium dioxide with different crystal forms The experimental synthesis conditions and intrinsic viscosity measurement results of PET polyester are shown in Table 3.
[0063] The optimal final polycondensation reaction temperature of 280 °C and catalyst concentration of 0.2‰ were obtained through screening experiments for polyester synthesis. Hexagonal germanium dioxide and self-made tetragonal germanium dioxide were selected as catalysts. Generally, for polyester catalysts, under the same conditions (same polycondensation temperature, same catalyst concentration, and same polycondensation time), the higher the intrinsic viscosity of the prepared PET polyester, the higher the catalytic activity of the catalyst. Table 3 shows that, under the same reaction conditions, the intrinsic viscosity of PET1 polyester prepared using tetragonal germanium dioxide catalyst was 0.429 dL / g, which is higher than the intrinsic viscosity of PET2 polyester prepared using hexagonal germanium dioxide catalyst (0.402 dL / g), and the molecular weight is also larger. This further indicates that the tetragonal germanium dioxide catalyst has higher activity than the hexagonal germanium dioxide catalyst, which is consistent with the analysis showing that tetragonal germanium dioxide has more oxygen defects than hexagonal germanium dioxide.
[0064] Table 3 PET Synthesis Conditions and Intrinsic Viscosities
[0065] Example 4: Optical property analysis of PET polyester The polyester PET1 and PET2 obtained after the final polycondensation reaction at a final polycondensation reaction temperature of 280 °C, a catalyst concentration of 0.2‰, and a polycondensation time of 3.5 h were coated onto a flat surface using a coater to form a 0.50 mm thick polyester film, with an actual thickness of 0.48 mm.
[0066] The transmittance of PET1 and PET2 was measured using a UV spectrophotometer in transmittance mode. The results are as follows: Figure 6 As shown, the transmittance of PET1 is 82.3%, which is higher than that of PET2 (78.2%). This indicates that the PET polyester prepared by the tetragonal germanium dioxide catalyst has better transparency. This is presumably due to the fact that the PET polyester prepared by the tetragonal germanium dioxide catalyst is more regular, has fewer impurities, and fewer crystalline regions.
[0067] Figure 7 The chromaticity diagrams for the two PET polyesters are shown. In terms of whiteness, PET1 has an L value of 92.2, slightly better than PET2. However, in terms of yellowness, PET1 has a lower b value of 4.45, a decrease of 16.67% compared to PET2, which is significantly better. This indicates that the tetragonal germanium dioxide catalyst produces fewer side reactions, resulting in a lower content of byproducts containing yellowing groups such as aldehydes. In conclusion, PET1 prepared using tetragonal germanium dioxide as a catalyst is superior to PET2 prepared using hexagonal germanium dioxide as a catalyst in both intrinsic viscosity and chromaticity.
[0068] Example 5: Thermal Performance Analysis of PET Polyester TGA spectra can determine the mass change of PET polyester when heated. Figure 8 These are TGA spectra of PET polyester samples prepared using germanium dioxide with different crystal forms as catalysts at 30-550 °C. Figure 8 It can be seen that the thermal degradation of PET1 and PET2 polyesters is almost the same, with the degradation temperature range being basically between 380-470 ℃. The 5% weight loss temperatures of PET1 and PET2 are 396.8 ℃ and 392.9 ℃, respectively, and the maximum weight loss temperature is around 460 ℃.
[0069] Figure 9 DTG spectra of PET polyester samples prepared with germanium dioxide catalysts of different crystal forms at 30-550 °C. Figure 9 It can be seen that although the maximum weight loss rate of PET1 is slightly higher than that of PET2, the temperature at which the maximum weight loss rate of PET1 occurs is 430.8 ℃, which is higher than that of PET2 (424.4 ℃). This is because hexagonal germanium dioxide has slightly stronger degradation reactivity than tetragonal germanium dioxide. Under the influence of hexagonal germanium dioxide, PET2 underwent degradation earlier, resulting in the difference in the curves. Furthermore, the thermal weight loss of PET polyester is due to the volatilization of small molecules remaining in the polyester itself and the thermal breakage of ester bonds, generating terminal carboxyl and hydroxyl groups, which in turn lead to the volatilization of small molecule products. The higher temperature at which the maximum weight loss rate of PET1 occurs, and the combination... Figure 8 It can be seen that the 5% weight loss temperature of PET1 is higher than that of PET2, and PET1 has a greater final residual mass, both indicating that PET1 polyester has a more stable structure and better stability. At the same time, it has fewer small molecule impurities remaining, indicating that PET1 polyester has fewer impurities, which is consistent with the light transmittance test results.
[0070] The DSC curve can intuitively reflect the crystallization properties, melting behavior, and melt crystallization behavior of PET samples. The glass transition temperature (T0) of the PET sample can be obtained from the DSC curve. g ), cold crystallization temperature (T) c ), melting point (T) m ), melt cooling crystallization temperature (T) mc ), enthalpy of cold crystallization (Δ H c ), enthalpy of fusion (Δ H m ), thermal crystallization enthalpy (Δ H mc ) and other characteristics.
[0071] Figure 10 The DSC spectra of PET1 prepared with tetragonal germanium dioxide as a catalyst and PET2 prepared with hexagonal germanium dioxide as a catalyst are shown at heating rates of 10 °C and cooling rates of 10 °C, respectively. Figure 10 Figures a and b in the middle are the heating curves of PET1 and PET2, respectively. Figure 10 As shown in Figures a and b, there is a peak around 70 °C, with step-like height variations on both sides of the peak. This is due to the heat absorption caused by PET1 and PET2 transitioning from a harder glassy state to a softer, more elastic state. The temperature corresponding to the midpoint of the step height variation is the glass transition temperature. Therefore, we can determine the Tg of PET1. g The T value of PET2 is 68.5 °C. g The temperature is 64.0 ℃. The T value of PET1 g T higher than PET2 g This is presumably due to the difference in intrinsic viscosity between the two types of PET polyesters. PET1 has a higher intrinsic viscosity, resulting in longer molecular chains, stronger interactions between the chains, and potentially more chain entanglement. Therefore, the chain segments have to overcome greater resistance to movement, requiring a higher temperature.
[0072] from Figure 10 As shown in Figures a and b, the DSC curve of PET1 exhibits an exothermic peak at 127.0 ℃, while that of PET2 appears at 120.9 ℃. The presence of this peak indicates the presence of amorphous PET within the original PET polyester. The temperature corresponding to this peak value is the cold crystallization temperature; under these conditions, PET releases heat from its amorphous state and rearranges to transform into a partially crystalline state. The Tc of PET2... c The temperature is lower because PET2 has shorter molecular chains, less interaction between molecular chains, and less chain entanglement, making it easier for chain segments to move, resulting in a faster crystallization rate and thus a lower crystallization temperature. The integral area of the peak corresponding to this temperature is the enthalpy of cold crystallization, so the Δcrystallization of PET1 is lower. H c The Δ value of PET2 is 38.9 J / g. H c It is 41.3 J / g.
[0073] Depend on Figure 10 As shown in Figure a, a large endothermic peak appears at 247.7 ℃. Figure 10 A large endothermic peak also appears at 240.4 ℃ in Figure b. This peak is the melting peak of the crystal, and the temperature corresponding to this peak is the melting point of polyester. PET1 has a higher melting point and a narrower peak, which to some extent indicates that PET1 has fewer impurities and is more stable. The integral area value of this peak is the enthalpy of fusion, and the Δfusion of PET1 is... H m The Δ value of PET2 is 54.5 J / g. H m It is 57.5 J / g.
[0074] Figure 10 Figures c and d show the cooling curves of PET1 and PET2, respectively. Figure 10 As can be seen from graphs c and d, there is only one peak, the temperature of which is the melt cooling crystallization temperature of PET1. mc The T value of PET2 is 194.5 °C. mc The temperature was 190.2℃. When the temperature of PET1 decreased... mc A higher T value indicates better regularity and flexibility of the PET1 molecular chain, and fewer impurities. At this temperature, PET polyester gradually arranges itself from the molten state to form regular crystals. The T value of PET1... mc A higher T value indicates a faster crystallization rate, allowing for earlier crystallization in the preparation of highly crystalline PET, shortening cooling time, and improving efficiency. Furthermore, the T value of PET1... mc The higher temperature and ability to crystallize at higher temperatures also indicate that its structure is relatively more stable than PET2 at high temperatures. The integral area of this peak is the enthalpy of thermal crystallization. The ΔE of PET1... H mc The Δ value of PET2 is 48.8 J / g. H mc The thermal enthalpy of PET2 is 49.1 J / g, which is slightly higher than that of PET2, indicating that PET2 may form crystals to a greater extent.
[0075] The various characteristic parameters obtained from the DSC curves of PET1 and PET2 are summarized in Table 4. The crystallinity was calculated using Formula 4 based on the enthalpy of cold crystallization and the enthalpy of melting. The results are shown in Table 4. The crystallinity of PET1 is 11.14%, slightly lower than that of PET2 (11.57%). Generally, the lower the crystallinity of PET, the greater its transparency. The crystallinity results are also consistent with the previously measured transparency results.
[0076] Table 4. DSC analysis results of PET samples
[0077] Example 6: Analysis of the Crystallization Properties of PET Polyester Crystallization properties play an important role in subsequent processing and predicting material properties. Preliminary calculations using DSC testing showed that PET1 and PET2 had low crystallinity. However, this calculation was affected by the DSC test results and the theoretical enthalpy of melting. Therefore, XRD testing was conducted to verify the crystallization properties of the prepared PET1 and PET2. Figure 11 The XRD patterns are shown for two groups of PET polyesters and two groups of heat-treated PET polyesters.
[0078] The samples exhibited low crystallinity, predominantly consisting of amorphous polyester, consistent with DSC results. After heating both groups of polyesters at 140℃ for 0.5 h followed by slow cooling, X-ray diffraction was performed, revealing diffraction peaks. Comparison with standard PET cards showed that 16.4° and 17.5° corresponded to the 010 crystal plane, 21.6° and 22.7° to the 100 crystal plane, 25.8° to the 110 crystal plane, and 32.6° to the 021 crystal plane, indicating that amorphous polyesters can be processed into crystalline PET polyesters under certain conditions.
Claims
1. A method for preparing a polyester, comprising the following steps: S1, obtaining an esterification product by esterification reaction of a binary acid and a binary alcohol; S2, obtaining a polyester by polycondensation reaction of the esterification product in the presence of a catalyst; the catalyst is prepared by the following method: 1) dispersing a hexagonal germanium dioxide raw material in an acidic aqueous solution to form a reaction mixture; 2) placing the reaction mixture in a hydrothermal reactor for hydrothermal reaction to obtain the catalyst; the hydrothermal reaction is carried out under the following conditions: the reaction temperature is 120-240℃, the reaction time is 24-48h, and the pH value is 1-3.
2. The method of claim 1, wherein: Before dispersing the hexagonal germanium dioxide raw material in the acidic aqueous solution, a step of calcining pretreatment of the hexagonal germanium dioxide raw material is further included; the calcining pretreatment is carried out at 500-600℃ for 4-8h.
3. The method of claim 2, wherein: The reaction temperature of the hydrothermal reaction is 120-80℃.
4. The production method according to any one of claims 1 to 3, characterized by: The hydrothermal reaction is carried out under the following conditions: the reaction temperature is 240℃, the reaction time is 36h, and the pH value is 3; the acidic aqueous solution is a sulfuric acid aqueous solution.
5. The method of any one of claims 1-4, wherein: The binary acid is terephthalic acid; the binary alcohol is ethylene glycol.
6. The production method according to any one of claims 1 to 5, characterized by: The polycondensation reaction is carried out under the following conditions: the amount of the catalyst is 0.10‰-0.30‰ of the mass of the ethanedioic acid, the temperature is 270-290℃, the time is 3.0-4.5h, and the reaction is carried out under vacuum.
7. The polyester prepared by the method of any one of claims 1-6.
8. The polyester according to claim 7, characterized in that: The intrinsic viscosity of the polyester is not less than 0.425 dL / g. The polyester has at least one of the following optical properties: the light transmittance is not less than 82%; the yellowness b value is not higher than 4.5; the whiteness L value is not less than 92; The polyester has at least one of the following thermal properties: the glass transition temperature is not less than 68℃; the cold crystallization temperature is not higher than 127℃; the melting point is not less than 247℃; the crystallinity measured by differential scanning calorimetry is not higher than 12%.
9. A polyester product, which is a film, a fiber or a bottle piece, prepared from the polyester of claim 7.